Toxoplasma gondii Seroprevalence and Risk Factors in Feline Patients Admitted to a Small Animal Veterinary Teaching Hospital in Central Germany over 11 Years (2012–2023) - Nils Altner; Laura Kemmling; Zaida Rentería-Solís; Anna Obiegala; Simone A. Fietz; Romy M. Heilmann (Pets)
Toxoplasma gondii is a protozoan parasite in cats that can be a cause of zoonotic concern due to sheding infectious and highly resistant oocysts. Clinical toxoplasmosis is rare in cats and can occur with mild to severe clinical signs or even fatal outcomes. T. gondii immunoglobulin M (IgM) or IgG is an indicator of ongoing or prior infection. Information about T. gondii occurrence in the domestic cat population, primary clinical concerns about affected cats, and potential risk factors is scarce in Germany. This retrospective study explored data from 174 feline patients (≥12 weeks old) presented to a tertiary veterinary care facility in central Germany between 2012 and 2023. T. gondii serological status, determined as part of the cats’ routine diagnostic evaluation, was assessed in relation to patient characteristics, environmental factors, medical history data, and clinical diagnosis. Neurological (57%), locomotor (25%), and ocular signs (11%) were common, and older age was associated with the presence of IgG (p = 0.008). Sex had no significant effects on T. gondii antibody positivity (p = 0.865). More outdoor cats than indoor-only cats were T. gondii IgG-positive (p = 0.021), and IgG-seropositive animals received a canned/wet diet more often than a dry kibble diet (p < 0.0001). Clinical representations aligned with previous studies, and age, choice of food, and outdoor living (p = 0.021) were significant predisposing factors.